Contrast-enhanced Ultrasound Features of Intrahepatic Cholangiocarcinoma: A New Perspective - Chen, Tianjiao (Sci Rep, 2019)
The objective of this study was to illustrate our specific findings for intrahepatic cholangiocarcinoma (ICC) lesions on contrast-enhanced ultrasound (CEUS). In this study, 21 patients at our hospitals with pathologically proven ICC and CEUS data were retrospectively enrolled. General clinical data of the patients, and features of lesions on conventional and contrast-enhanced ultrasound were recorded. Two experienced radiologists retrospectively reviewed all images by consensus. On gray-scale sonography, hypoechoic, isoechoic and hyperechoic lesions accounted for 85.7%, 9.5% and 4.8%, respectively, of all lesions. Hypovascular patterns were found for 95.2% of the lesions on color Doppler flow imaging. During the arterial phase of CEUS, heterogeneous hyperenhancement, homogeneous hyperenhancement, rim-like hyperenhancement, isoenhancement and hypoenhancement were observed for 61.9%, 19.0%, 9.5%, 4.8%, 4.8% of the lesions, respectively. During the portal venous and late phases, 85.7% and 95.2% of the lesions, respectively, exhibited hypoenhancement. In addition, 66.7% of the ICC lesions exhibited washed-out interiors but little decrease in enhancement at the periphery during the portal venous phase, resulting in the formation of a hyperenhanced peripheral rim. In conclusion, the rim sign in the portal venous phase of CEUS could help diagnose ICC. This trait could be related to the infiltrating growth pattern of ICC.